Analytical methods for food additives - Wood, Roger , 1945- (Woodhead Publishing in food science and technology, 2004)
This volume discusses methods of analysis for 30 major additives where methods are incomplete or deficient. In each case the authors review current techniques, their respective strengths and weaknesses, method procedures and which method to adopt